Genome-wide association study identifies quantitative trait loci regions involved in muscle acidic profile in Large White heavy pigs. (10th July 2020) - Catillo, G.; Zappaterra, M.; Zambonelli, P.; Buttazzoni, L.; Steri, R.; Minelli, G.; Davoli, R.
Abstract : The widespread use of genome-wide association studies resulted in the discovery of genomic regions associated with fatty acid (FA ) composition in different porcine tissues, but little information exists about the genes involved in FA composition of meat obtained from heavy pigs selected for the production of Italian dry-cured hams. To this objective, we genotyped with a single nucleotide polymorphism (SNP ) panel 795 Italian Large White heavy pigs to identify the markers and genomic regions associated with Semimembranosus muscle FA profile. Heritability estimates for intramuscular fat FA profile were of low-to-moderate magnitude, suggesting that these traits may be improved with genomic selection. On the whole, 45 SNPs were significantly associated with 14 FAs, and 4 of them (ALGA008109, ALGA0081097, CASI0010164 and SIRI0000267) were associated with more than 1 FA. The palmitoleic : palmitic and oleic : stearic ratios displayed the highest number of significant markers and the most significant associations (Bonferroni adjusted P < 5.00E−07). Of particular interest, the palmitoleic : palmitic ratio was strongly associated with markers located at 111 to 114 Mb on chromosome 14, in the same chromosomal region where Stearoyl-CoA desaturase Δ9 ( SCD ) gene is located. Several significant chromosomal regions were found; some of them harbour key genes playing pivotal roles in FA desaturation and elongation, such as SCD and some members of the Elongation of Very Long-Chain FA ( ELOVL ) gene family. The results suggest that the identification of causal mutations in these regions may provide a set of markers useful for selection schemes aimed at improving FA composition in pork products.